PERAN PERBANKAN SYARIAH TERHADAP PERTUMBUHAN EKONOMI SEKTOR RIIL DI INDONESIA - Leza Febrika (Jurnal Al Wadiah, 2023)
This exploration expects to look at and examine the job of sharia counts on genuine area monetary development in Indonesia. The job of sharia banking is estimated utilizing outsider assets (DPK) and supporting gave (PYD), while genuine area financial development is estimated by total national output (Gross domestic product). 387 time series data from economic and financial statistics and sharia banking statistics are used in this study. Indonesia during the exploration time frame 2008-2016 with month to month information as the data set. The multiple linear regression method was used to analyze the data. This exploration found that the sharia banking area supports genuine area financial development in Indonesia.